2009
DOI: 10.3928/01484834-20090515-04
|View full text |Cite
|
Sign up to set email alerts
|

Spiraling Evidence-Based Practice and Outcomes Management Concepts in an Undergraduate Curriculum: A Systematic Approach

Abstract: Preparing undergraduate nursing students to practice nursing in the 21st century requires a focus on the development of evidence-based practice and outcomes management knowledge and skills throughout the nursing curriculum. To this end, seven learning activities were created that spiral and increase in complexity while building on previously acquired skills. Working in teams and practicing team-building techniques, students learned how to develop a clinical question, search the literature, synthesize the curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
11

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 13 publications
0
9
0
11
Order By: Relevance
“…Compared with students in the control group (traditional lecture), q qqq students in the experimental group (innovative teaching approach) had more positive attitudes toward research, higher levels of classroom engagement and value of teams, more involvement in self-directed learning, and higher skill levels in eight core competencies in nursing. Nurse scholars have proposed that an evidence-based learning context for research learning will set a foundation for the following vital skills that students will need in future clinical practice: critical thinking, lifelong learning to continue professional growth, team communication and collaboration, understanding how to effectively disseminate and incorporate research findings into clinical practice, and adherence to ethical values required in research study (Callister et al, 2005;Clark et al, 2009;Ross et al, 2009). Similar to previous studies, this study found that nursing students are more engaged in research class and interact and collaborate with others as a team when innovative, interactive assignments are applied (Clark et al, 2009;Meeker Clayton, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with students in the control group (traditional lecture), q qqq students in the experimental group (innovative teaching approach) had more positive attitudes toward research, higher levels of classroom engagement and value of teams, more involvement in self-directed learning, and higher skill levels in eight core competencies in nursing. Nurse scholars have proposed that an evidence-based learning context for research learning will set a foundation for the following vital skills that students will need in future clinical practice: critical thinking, lifelong learning to continue professional growth, team communication and collaboration, understanding how to effectively disseminate and incorporate research findings into clinical practice, and adherence to ethical values required in research study (Callister et al, 2005;Clark et al, 2009;Ross et al, 2009). Similar to previous studies, this study found that nursing students are more engaged in research class and interact and collaborate with others as a team when innovative, interactive assignments are applied (Clark et al, 2009;Meeker Clayton, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In adopting evidencebased practice, healthcare professionals examine research findings and quality improvement data that provide appropriate, scientific information to help professionals make effective clinical decisions, avoid simple habitual practice, and enhance clinical quality of care (Evidence-Based Medicine Working Group, 1992). Applying innovative teaching strategies combining collaborative and evidence-based learning is therefore conducive to the development of future professional skills such as team cooperation and communication, critical thinking, and incorporating research findings into clinical practice (Clark, Stanforth, & Humprhie, 2009;Poston, 2002;Ross, Noone, Luce, & Sideras, 2009). These abilities require an initial acknowledgment and understanding of the importance of research to the professional nursing practice.…”
Section: Purposementioning
confidence: 99%
“…Studiene belyste ulike typer av spørsmål og hadde varierende kvalitet. Forskningsdesignene varierte fra en litteraturgjennomgang (19), to kvasieksperimentelle studier (20,21), en artikkel med aksjonsforskningsdesign (22) en kohortstudie (23), to beskrivende (24,25) og fire casestudier (26)(27)(28)(29). Casestudiene, aksjonsforskningsstudiet og en av de beskrivende studiene (25) omhandlet organisering og laeringsaktiviteter om KBP i utdanningen og gir innsikt i hvordan dette kan ha positiv innvirkning på enkeltstudenters laering.…”
Section: Resultaterunclassified
“…Hvor grundig laeringsaktivitetene ble beskrevet varierte i de inkluderte studiene. De fleste kombinerte forelesninger og/eller e-laering med påfølgende oppgaveløsning (20)(21)(22)(23)(24)(26)(27)(28)(29). En studie (20) undersøkte effekten av et interaktivt undervisningsopplegg i KBP over ett semester mot slutten av utdanningen.…”
Section: Aksjonsforskningunclassified
“…Both nurse educators and nurse leaders have important roles to play in this regard. Nurse educators, in particular, have the dual responsibility of identifying creative and innovative approaches to teaching nursing students the skills required for EBP (Ferguson & Day, 2005;Kim, Brown, Fields, & Stichler, 2009;Ross, Noone, Luce, & Sideras, 2009) while at the same time ensuring that nursing pedagogy itself is evidence based (Earle & Myrick, 2009;Ferguson & Day, 2005). Nurse leaders can play a significant role in creating a culture for EBP and empowering nurses to develop the skills needed for EBP.…”
Section: Future Pathways For Nursingmentioning
confidence: 99%